Infant Fecal Fermentations with Galacto-Oligosaccharides and 2'-Fucosyllactose Show Differential Bifidobacterium longum Stimulation at Subspecies Level - Cordula Lindner; Ellen Looijesteijn; Helmie van Dijck; Ingeborg Bovee-Oudenhoven; Margreet Heerikhuisen; Tim J. van den Broek; Massimo Marzorati; Vassilis Triantis; Arjen Nauta (MDPI AG, 2023)
The objective of the current study was to evaluate the potential of 2'-FL and GOS, individually and combined, in beneficially modulating the microbial composition of infant and toddler (12-18 months) feces using the micro-Matrix bioreactor. In addition, the impacts of GOS and 2'-FL, individually and combined, on the outgrowth of fecal bifidobacteria at (sub)species level was investigated using the baby M-SHIME® model. For young toddlers, significant increases in the genera Bifidobacterium, Veillonella, and Streptococcus, and decreases in Enterobacteriaceae, Clostridium XIVa, and Roseburia were observed in all supplemented fermentations. In addition, GOS, and combinations of GOS and 2'-FL, increased Collinsella and decreased Salmonella, whereas 2'-FL, and combined GOS and 2'-FL, decreased Dorea. Alpha diversity increased significantly in infants with GOS and/or 2'-FL, as well as the relative abundances of the genera Veillonella and Akkermansia with 2'-FL, and Lactobacillus with GOS. Combinations of GOS and 2'-FL significantly stimulated Veillonella, Lactobacillus, Bifidobacterium, and Streptococcus. In all supplemented fermentations, Proteobacteria decreased, with the most profound decreases accomplished by the combination of GOS and 2'-FL. When zooming in on the different (sub)species of Bifidobacterium, GOS and 2'-FL were shown to be complementary in stimulating breast-fed infant-associated subspecies of Bifidobacterium longum in a dose-dependent manner: GOS stimulated Bifidobacterium longum subsp. longum, whereas 2'-FL supported outgrowth of Bifidobacterium longum subsp. infantis.